2021
DOI: 10.1021/acsami.1c18777
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Sodium Water-in-Salt Electrolyte and Carbon Electrode Interface from Electrochemistry and Operando Raman Studies

Abstract: Comprehensive electrochemical and operando Raman studies are performed to investigate the electrochemical stability window (ESW) of supercapacitors filled with normal (salt-in-water) and highly concentrated (water-in-salt, WiSE) electrolytes. Impedance and chronoamperometric experiments are employed and combined with cyclic voltammetry to correctly define the ESW for a WiSE-based device. The total absence of water-splitting resulted in phase angles close to −90° in the impedance data. It is verified that a 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…WiSE experimentally showed a larger electrochemical stability window (ESW) due to the formation of a solvent blocking interface (SBI) that allows spanning the cell voltage and specific energy. 10–12 We have observed that both work in a WVW up to 2.0 V, close to most 2.5 V organic electrolytes. 9 Considering this issue, most researchers used to work on the abuse voltage regime based only on eqn (1) and (2), where the device, instead of storing more energy, is in the working process of the degradation state.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…WiSE experimentally showed a larger electrochemical stability window (ESW) due to the formation of a solvent blocking interface (SBI) that allows spanning the cell voltage and specific energy. 10–12 We have observed that both work in a WVW up to 2.0 V, close to most 2.5 V organic electrolytes. 9 Considering this issue, most researchers used to work on the abuse voltage regime based only on eqn (1) and (2), where the device, instead of storing more energy, is in the working process of the degradation state.…”
Section: Introductionmentioning
confidence: 64%
“…The water-in-salt electrolytes (WiSEs) 5,6 and salt-in-water neutral aqueous electrolytes 7,8 have promised WVWs as wide as those of organic electrolytes. 9 Our group has observed several optimistic issues, [10][11][12] such as an increased stable working voltage window, close to 2 V, and greater safety due to the use of aqueous electrolytes compared to organic or IL electrolytes which are ammable and toxic. WiSE experimentally showed a larger electrochemical stability window (ESW) due to the formation of a solvent blocking interface (SBI) that allows spanning the cell voltage and specic energy.…”
Section: Introductionmentioning
confidence: 99%
“…Noting that the intensity of vibration peak at 932 cm À 1 increases with the rise of concentration, it is attributed to the interaction of AGGs in that the amount of groups of NaÀ OÀ Cl bonding increases in the order of ULCE, LCE and HCE. [26] Considering the similar coordination environments with AGGs, the vibration peaks at 893 cm À 1 and 898 cm À 1 are assigned to the interaction of ClO 4…”
Section: Resultsmentioning
confidence: 99%
“…[36] Notably, the promoted intensity of Raman signal about carbon material during the electrochemical process can be caused by the electrode polarization due to the reduced number of ions on the electrode surface, or the strong interaction between ion and carbon microstructure. [37,38] Besides, the D ion can be also calculated according to GITT curves in Figure S19 (Supporting Information) based on the following Equation ( 6):…”
Section: Electrochemical Mechanismmentioning
confidence: 99%